1999
DOI: 10.1152/jn.1999.82.3.1147
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Calcium Dependence of Glutamate Transmission in the Hippocampal CA1 Region After Brief Hypoxia-Hypoglycemia

Abstract: Using the model of hypoxia-hypoglycemia (HH) in rat brain slices, we asked whether glutamate transmission is altered following a brief HH episode. The HH challenge was conducted by exposing slices to a glucose-free medium aerated with 95% N2-5% CO2, for approximately 4 min, and glutamate transmission in the hippocampal CA1 region was monitored at different post HH times. In slices examined Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…The abovementioned putative hypoxia of slices in a submerged chamber or during preparation perhaps could have increased release probability. It has been demonstrated that glutamate release can be persistently increased in hippocampal slices after even a brief episode of severe hypoxia (Hsu and Huang, 1997;Ouanonou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The abovementioned putative hypoxia of slices in a submerged chamber or during preparation perhaps could have increased release probability. It has been demonstrated that glutamate release can be persistently increased in hippocampal slices after even a brief episode of severe hypoxia (Hsu and Huang, 1997;Ouanonou et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Because most studies involving hypoglycemia use glucose deprivation in combination with other insults (Vannucci & Yager 1992, Yager et al 1992, Ouanonou et al 1999, Breder et al 2000, Tekkok et al 2002, it is difficult to determine direct and indirect effects. In contrast, the data we present here represent effects of hypoglycemia only, using a single population of neurons, wherein direct action of glucose deprivation can more readily be observed.…”
Section: Discussionmentioning
confidence: 99%
“…A glass suction pipet (diameter of 10 mm) was used to transfer slices. We have previously shown that the slice transfer procedure causes no evident alterations in synaptic and intracellular activities of hippocampal pyramidal neurons (Ouanonou et al, 1999). Slice transfer alone (without cobalt incubation) did not induce epileptiform discharges (n = 10 slices).…”
Section: Methodsmentioning
confidence: 99%